An analysis of the credibility of an auditor’s report for commercial banks in making financing and investing decisions - Sigudu, Collen (Midlands State University, 2017)
This research was carried out to analyse the credibility of an auditor’s report for commercial banks in making financing and investing decisions. The usefulness of the audit report for commercial banks in making financing and investing decisions has been called into question after many banks have been issued with unqualified reports, and still went through liquidation some few months later. The main objective of this research was to analyse the usefulness of audit report for Commercial banks in making financing and investing decisions. In achieving this objective, the research consulted literature from various authorities to gain in-depth knowledge of the subject. The main literature was from Durendez (2003) who suggested that audit reports are failing to address financial risk on banks and rendering them not useful for decision making. Also the conceptual framework model from Gray and Jenkins (2012) who stated that there is a direct relationship between audit report and decision making was considered in developing the hypothesis .The information contained in the audit report is considered inadequate in making financing and investing decisions. This study targeted to explore how important the audit report is for Commercial banks in making financing and investing decisions. The research used a sample size of four commercial banks, where both primary and secondary sources of collecting data were used. The respondents were asked about the usefulness of audit report and how different types of audit reports (Unqualified, qualified, adverse and disclaimer) influence their financing and investing decisions. The research finds out that banks have more confidence in making financing and investing decisions using an unmodified report over modified reports. The research also looked into the various elements of audit report such as audit opinion, and going concern opinion that banks considered to be very crucial for decision making. The results indicated that going concern opinions are not being properly carried out as many banks are being liquidated after a positive opinion has been expressed. The research recommends that the information content provided in the audit need to be adjusted to meet the individual organization needs. To justify the validity and reliability of the finding a chi-square test was used to test the relationship between the two variables of the research hypothesis. A relationship between audit report and financing and investing decisions was established, and the research concluded that audit reports are useful in making financing and investing decisions, but the extend varies with the type of audit report issued.